HAMBATAN DINAS PENDIDIKAN PROVINSI BENGKULU DALAM PENGINTEGRASIAN PENGELOLAAN SMA DAN SMK - Herles Tiana; Aliman Aliman; Manap Somantri (Manajer Pendididikan, 2017)
The purpose of writing the article is to describe the barriers and solutions in the management of high school and vocational integration into the province of Bengkulu. The method used is descriptive qualitative analysis. The subjects used in are: Head, Head, Head of Sector Dikmen, and Principal of SMA and SMK. The tools used in the collection of data is by using interviews, documentation, and observation. The results of the study are as follows: Readiness Education Department of Bengkulu province in carrying out the implementation of actional rule No. 23 of 2014, is now being preparing for the transition of authority from the district / city to the provinces to collect data on the number of high school teachers and vocational school, the school's assets, the number of supervisors, as well as matters more about the switch. This data collection has been conducted from February to April 2016 yesterday, then on October 3, 2016 will be the handover of district / city government to the provinces.